Upaya Guru Tahfidz Dan Siswa Dalam Meningkatkan Kualitas Hafalan Al Qur’an Siswa Kelas XI Di SMA Islam Terpadu Permata Hati Kota Tebing Tinggi - Widari, Ike; Pratiwi, Indah Dina; Kasran (At-Tarbiyah: Journal of Islamic Religious Research and Education, 2024)
This research is motivated by the many cases of memorizers of the Qur'an who have weak memorization quality, such as forgetting verses that have been memorized and the ability to read the Qur'an that is not in accordance with the rules of tajwid. The objectives of this study are (1) to determine the implementation of tahfidz learning at Permata Hati Integrated Islamic High School, Tebing Tinggi City, (2) to determine what obstacles are experienced by tahfidz teachers and students in improving the quality of memorization of class XI students at Permata Hati Integrated Islamic High School, Tebing Tinggi City, (3) to determine the efforts of teachers and students in improving the quality of memorization of class XI students at Permata Hati Integrated Islamic High School, Tebing Tinggi City. The method used in this study is a descriptive research method using a qualitative approach. Data collection techniques through interviews, observation and documentation. The final results obtained in this study are: Efforts made by tahfidz teachers in improving the quality of memorization of class XI students at Permata Hari Integrated Islamic High School are motivating students, improving students' tahsin , telling students easy methods in ziyadah and muraja'ah, providing students with an understanding of the manners and blessings of the Qur'an, praying for students, working together with parents/guardians of students, asking students to muraja'ah independently until memorization is really fluent, asking students to listen to murattal, aligning students' readings with the Wafa method or nada hijaz. Meanwhile, students' efforts to improve the quality of memorization are consistency, not delaying time in ziyadah and muraja'ah, making time for muraja'ah, doing muraja'ah of old memorization before adding new memorization, maintaining manners, avoiding sins, focusing when ziyadah and muraja'ah, memorizing with only one mushaf of the Qur'an, managing time between ziyadah and muraja'ah